Colonic lithobezoar: a rare cause of partial intestinal obstruction - Boybeyi, Ozlem; Albayrak, Meryem; Aslan, M Kemal; Soyer, Tutku (The Turkish Journal of Pediatrics, 2013)
Bezoar is the accumulation of indigestible foreign substances in the digestive tract and a rare cause of intestinal obstruction in children. The accumulation of stones within the digestive system is called lithobezoar, and the colon is the rarest site for accumulation. A 13-year-old female patient was admitted to our hospital with colicky abdominal pain and constipation. She had been unable to pass her stool for the last six days and had passed stones-containing stools previously. She had a history of pica and iron-deficient anemia. The case is presented to discuss the diagnostic and therapeutic features of partial colonic obstruction secondary to colonic lithobezoar accumulation.